2006
DOI: 10.1080/10826080600846250
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Research on the Role of Alcohol Consumption and Related Risks in the Prevention and Treatment of HIV_AIDS

Abstract: This article is a review of some of the major epidemiological, behavioral, biological, and integrative prevention research issues and priorities in the area of HIV/AIDS and alcohol consumption. Drinking alcohol increases both the risk for infection with HIV and related illnesses and the morbidity and mortality of patients who progress to AIDS. New and improved measurement procedures have helped in assessment of the complex patterns of alcohol use, identification of intervening explanatory mechanisms for risk b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 223 publications
3
110
1
Order By: Relevance
“…multiple sexual partners, unprotected vaginal and anal intercourse, inconsistent condom use, and paying for or selling sex) (Alem, Kebede, Mitike, Enqusellase & Lemma, 2006;Lurie et al, 2008;Weiser et al, 2006). A number of theories have been proposed to explain the complex relationship between alcohol consumption and sexual risk behaviour, including the psychoactive effects of alcohol on sexual decision-making, expectations surrounding the effects of alcohol, high-risk settings and risk-taking personality characteristics (Bryant, 2006;Corte & Sommers, 2005;Kalichman, Simbayi, Jooste, Cain & Cherry, 2006;Morojele et al, 2006).…”
Section: Alcohol Use and Hiv Sexual Risk Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…multiple sexual partners, unprotected vaginal and anal intercourse, inconsistent condom use, and paying for or selling sex) (Alem, Kebede, Mitike, Enqusellase & Lemma, 2006;Lurie et al, 2008;Weiser et al, 2006). A number of theories have been proposed to explain the complex relationship between alcohol consumption and sexual risk behaviour, including the psychoactive effects of alcohol on sexual decision-making, expectations surrounding the effects of alcohol, high-risk settings and risk-taking personality characteristics (Bryant, 2006;Corte & Sommers, 2005;Kalichman, Simbayi, Jooste, Cain & Cherry, 2006;Morojele et al, 2006).…”
Section: Alcohol Use and Hiv Sexual Risk Behavioursmentioning
confidence: 99%
“…In addition, the effect of alcohol on liver function may affect its ability to metabolise certain HIV medication, thus reducing their therapeutic efficacy. This, together with non-compliance to ART, not only results in poorer HIV treatment outcomes, but can also lead to the development of drug-resistant HIV strains (Bekker, 2005;Bryant 2006). …”
Section: Alcohol Use and Hiv Infection Disease Progression And Treatmentioning
confidence: 99%
“…Studies have shown that immediately after consuming alcohol, the likelihood of risky sexual activity increases, as alcohol is thought to decrease an individual's ability to consider negative consequences [56]. Adolescent drinkers have been found to be more likely to report multiple sexual partners, inconsistent condom use, sexually transmitted infections, and unplanned pregnancy [8,12,34].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 20,000 offenders with a recent history of injection drug use enter the New York City criminal justice system every year (Belenko et al 2004). Elevated sexual HIV risk behaviors have been associated with excessive use of alcohol (Bryant 2006), marijuana and cocaine (Braithwaite and Stephens 2005), methamphetamines (Molitor et al 1998;Wohl et al 2002), and club drugs (Colfax and Guzman 2006). Risky sexual practices were also found to be associated with crack cocaine use and polysubstance abuse (Booth et al 1993;Campsmith et al 2000;Chesney et al 1998;Stephens et al 2004).…”
mentioning
confidence: 99%